Lexical text relations and the psychological implications of repetition (Texas Journal of Multidisciplinary Studies, 2024)
This research falls within the science of linguistics, which studies the text and its subject, language. What it means from the text is its language. Since the text is an integrated linguistic unit, this integration is achieved by textual tools that support each other to achieve textual cohesion. The text is linked by relationships called textual relationships, and these relationships interrelate with each other. This coherence results in a coherent text. The reasons for choosing the research are the scarcity and novelty of the research